2006
DOI: 10.1177/152692480601600109
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Study of the Cognitive, Academic, and Behavioral Functioning of Pediatric Cardiothoracic Transplant Recipients

Abstract: On measures of cognitive functioning, 46% showed significant delays (> 2 SD below the normative population). Of those eligible for academic testing, 78% fell within the average range (within 1 SD of the normative population) for reading and spelling, and 57% fell within the average range for math. Twenty-seven percent of mothers, 11% of fathers, and 17% of teachers rated subjects as having significant behavioral concerns. Results highlight the need for close contact between transplant teams and school personne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The findings of Serrano-Ikkos et al 3 suggest that older age has a negative effect on long-term psychosocial functioning; however, psychosocial outcomes were not related to age or time since transplant according to other reports. 4,17,18 Wray et al 2 assessed heart transplant recipients at 12 months and 3 years after transplant and found stability in psychologic functioning over time. Although psychosocial QOL was significantly correlated with symptoms, symptoms were uncommon in our study.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The findings of Serrano-Ikkos et al 3 suggest that older age has a negative effect on long-term psychosocial functioning; however, psychosocial outcomes were not related to age or time since transplant according to other reports. 4,17,18 Wray et al 2 assessed heart transplant recipients at 12 months and 3 years after transplant and found stability in psychologic functioning over time. Although psychosocial QOL was significantly correlated with symptoms, symptoms were uncommon in our study.…”
Section: Discussionmentioning
confidence: 98%
“…[21][22][23] Interestingly, the observed trouble solving math problems in our study is also consistent with objective measurement of arithmetic scores in heart transplant recipients reported by others. 2,17 Identification of developmental or cognitive deficits after transplant is important to design interventions to optimize school functioning.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in the US implemented standardized measures to evaluate cognitive, academic and behavioural function in individuals who underwent a paediatric cardiothoracic transplant and compared participants' scores to same age normative samples (Brosing et al, 2006). Results for cognitive functioning confirmed that typically individuals fell within the low average to average score.…”
Section: Social Outcomesmentioning
confidence: 84%
“…All the children miss school and for some this can amount to months of education, which has been observed in decreased academic performance (Brosing et al, 2006). In previously conducted research assessing psychological function and social development, factors such as physical limitations, living with a progressive terminal condition, school absenteeism and the lack of social interaction have not been taken into account.…”
Section: Social Outcomesmentioning
confidence: 99%
See 1 more Smart Citation